Redefenisi Kepala Sekolah sebagai Learning Leader melalui Integrasi Kepemimpinan Instruksional dan Transformasional: Kajian Literatur (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The role of the principal in educational management has undergone significant changes in line with the dynamics of 21st-century needs. Demands for improved learning quality have led to the emergence of a new paradigm that positions the principal not merely as an administrative leader but as a learning leader capable of facilitating a culture of continuous learning within the school environment. This study aims to reflect on and reformulate the principal's strategic role through the integration of two leadership approaches: instructional leadership, which emphasizes strengthening the learning process, and transformational leadership, which focuses on vision, motivation, and empowerment of all school members. The method used is a literature review of 26 national and international scientific articles published in the last ten years. The results of the study indicate that the synthesis of these two leadership models strengthens the principal's capacity to create a collaborative, adaptive school climate oriented toward continuous improvement of educational quality. This research is expected to serve as a conceptual foundation for future school leadership development policies and practices.